Role of effective microorganisms on broiler performance and odor emission from litter in broiler chicken production - Miadu, Sbahle Sivetmbhea; Muritala, Ismaila; Fon, Fabian Nde; Suninyuy, Terence N (International Journal of Agriculture System, 2025)
Poultry production is a reliable animal protein source used in different communities. Malodor emitted from poultry houses limits their production and significantly contributes to air pollution. Mitigations are thus required to make broiler chicken production more environmentally friendly and productive. This study investigated the role of effective microorganism (EM) on broiler performance and odor emission from litter in broiler chicken production. A total of 180-day-old chicks were divided into four treatments: T0 (without EM-supplementation), T1 (EM-supplemented in water), T2 (EM-supplemented in feed), and T3 (EM-supplemented in water+feed), with three replicates of 15 birds each. Data on broiler performance, including water intake (WI), feed intake (FI), average weight gain (ADG), feed conversion ratio, and carcass characteristics, were measured and analyzed using one-way ANOVA in SPSS (version 25). Malodor agents were characterized by using gas chromatography. Significant (p<0.05) increase in WI and FI was delayed among chickens with EM treatments until 4th- 6th and 5th – 6th weeks, where T0 had lower (p<0.05) FI and WI, respectively. T3 had the highest (p≤0.05) increased ADG at the 5th and 6th weeks. Heart, wing, thigh, girth, and live weight did not differ (p>0.05) among treatments, while T0 had higher (p<0.05) liver and gizzard weight compared to the estimates from other groups. T0 recorded higher (p<0.05) gases, emitted from grower to finisher, compared with starter. EM treatment decreased (p<0.05) the number of gases emitted, with T3 recorded as the lowest. Thus, EM applications may alter the emission of odor-causing compounds in the broiler chicken litter without compromising its performance.